2008
DOI: 10.1093/hmg/ddn363
|View full text |Cite
|
Sign up to set email alerts
|

A loss-of-function variant of PTPN22 is associated with reduced risk of systemic lupus erythematosus

Abstract: A gain-of-function R620W polymorphism in the PTPN22 gene, encoding the lymphoid tyrosine phosphatase LYP, has recently emerged as an important risk factor for human autoimmunity. Here we report that another missense substitution (R263Q) within the catalytic domain of LYP leads to reduced phosphatase activity. High-resolution structural analysis revealed the molecular basis for this loss of function. Furthermore, the Q263 variant conferred protection against human systemic lupus erythematosus, reinforcing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 29 publications
12
111
2
2
Order By: Relevance
“…First, because the charge and hydrophobicity of surfaces surrounding the catalytic pocket vary considerably among PTPs (15,(18)(19)(20), we explored whether the addition of the polyarginine tag with a lipid tail restricts the selectivity of the peptides. A cell-penetrating version of peptide 1 (myristoyl-βAla-(Arg) 7 -EDNE-(pCAP)-TARE-NH 2 ; hereafter, SP1) was synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…First, because the charge and hydrophobicity of surfaces surrounding the catalytic pocket vary considerably among PTPs (15,(18)(19)(20), we explored whether the addition of the polyarginine tag with a lipid tail restricts the selectivity of the peptides. A cell-penetrating version of peptide 1 (myristoyl-βAla-(Arg) 7 -EDNE-(pCAP)-TARE-NH 2 ; hereafter, SP1) was synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…31 Another less frequent PTPN22 variant (R263Q), which has been associated with reduced risk for autoimmune disease, was observed in another patient. 32 Overall, the sequencing analysis revealed that PTPN22 and SHP-1 are not frequently mutated in CLL and that the PTPN22 autoimmunedisease risk variant is not more prevalent in CLL patients than in the general population. …”
mentioning
confidence: 92%
“…Importantly, the autoimmune-predisposing variant of Lyp appears to represent a gain-of-function mutation, leading to increased inhibition of T-cell signaling relative to the wild-type enzyme (12). Interestingly, a loss-of-function variant of PTPN22 has been linked to reduced risk of systemic lupus erythematosus (13). Hence, Lyp is emerging as a potential target for therapeutic intervention of a broad spectrum of autoimmune disorders.…”
mentioning
confidence: 99%